Rekonseptualisasi Nusyuz dan Syiqaq di Era Digital: Analisis Problematika dan Mekanisme Penyelesaian Modern: Penelitian - Firdaus, M. Ridho; Nelli, Jumni (Jurnal Pengabdian Masyarakat dan Riset Pendidikan, 2026)
The concepts of nusyuz (disobedience of husband or wife) and syiqaq (escalating disputes) are fundamental frameworks in the jurisprudence of munakahat for analyzing and resolving domestic conflicts. However, existing literature tends to focus on the conventional manifestations of these two concepts. This study aims to reconceptualize nusyuz and syiqaq in the context of the digital era, which has given rise to new forms of problematic issues. Using conceptual analysis methods based on primary sources of Islamic law and contemporary social theories, this article identifies and categorizes forms of "Digital Nusyuz," such as financial nusyuz through non-transparent online transactions, emotional nusyuz through social media interactions, and digital privacy violations as triggers of conflict. Furthermore, this article analyzes how the escalation of digital nusyuz can lead to more complex syiqaq. As a solution, a resolution model is proposed that integrates the role of traditional hakam (peacemakers) with digital literacy and online conflict mediation. The results of this study offer a new framework for legal practitioners, marriage counselors, and judges in Religious Courts to understand and resolve household problems rooted in interactions in the digital world, a contribution that is expected to fill the gap in contemporary Islamic family law studies.